Pengembangan Sistem Email Campaign Generator Menggunakan AI untuk Promosi Produk Baru - Angelica Indah Desviyani; Mela Revania; Alifha Yashinta Rachman; Muhammad Rafa Kuswanto; Muhammad Irsyad; Mohammad Givi Efgivia (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
In the contemporary digital landscape, the necessity for an AI-driven Email Campaign Generator is progressively vital for firms to enhance the promotion of new products. This sistem extracts the most recent product information from the database, employs a language model to create appropriate advertising descriptions, and subsequently automates the distribution of emails to the target demographic. The connection encompasses Airtable as the primary data repository, OpenAI for the creation of promotional content, and the Gmail API to facilitate the automation of the email distribution process. This technique enables marketing operations to be executed more efficiently and reliably, while minimizing time-consuming manual processes. The deployment results demonstrate that the sistem can generate compelling promotional content and automate the entire promotional procedure. This improvement is anticipated to assist organizations in broadening their marketing reach, expediting product information dissemination, and enhancing digital marketing methods that can swiftly respond to evolving demands.